KORESPONDENSI FONEMIS BAHASA BALI DAN BAHASA SUMBAWA - Riris Tiani (KAJIAN SASTRA, 2010)
Bali and Sumbawa belongs to Austronesian languages. Which the languages genetically have cognate. So there are shows sound changes, that is called phonemics correspondence. Sound changes in the Bali and Sumbawa languages happen with continuity. Based on the assumption, one of the method used to prove it is using comparative analysis by using phonemic correspondence technique. Based on the technique mentioned above, it was found that the formula phonemic correspondence in Bali and Sumbawa languages, those are: a. *a > /ə a / excpecially on position opened ultima and closed ultima, which is bilabial, palatal. b. *u > /u i / on closed ultima.